The Ecotheology of the Qur'an in Surah Ar-Rahman: The Balance of Nature as a Manifestation of Divine Grace - Harisatul Qibtiyah; Musolli Musolli (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to examine ecotheological values in QS. Ar-Rahman verses 1–12 and their relevance in building human ecological awareness. The global environmental crisis indicates that ecological damage is caused not only by technical factors, but also by human spiritual crises that weakens the harmonious relationship between man, God, and nature. This study employs a thematic interpretation approach with a descriptive qualitative method based on library research. The primary data source is QS. Ar-Rahman verses 1–12 analyzed through Tafsir Al-Misbah, Tafsir Fi Zhilalil Qur'an, and Tafsir Al-Azhar. The results reveal six main ecotheological values, namely divine mercy as the foundational principle, along with human stewardship, cosmic submission, balance (mizan), justice (al-qisth) and gratitude as derivative principles. These values constitute the concept of Qur'anic ecotheology, which emphasizes that nature is a manifestation of divine mercy that must be preserved by humans as vicegerents. This study concludes that integrating divine mercy and ecological awareness contributes to the formation of sustainable environmental ethics, indicating that addressing environmental crisis requires not only scientific approaches but also the internalization of Qur'anic values.